Identifikasi Nematoda Parasit pada Tanaman Wortel di Dataran Tinggi Malino, Sulawesi Selatan Berdasarkan pada Ciri Morfologi dan Morfometrik - Hishar Mirsam; Supramana Supramana; Gede Suastika (Jurnal Fitopatologi Indonesia, 2015)
Plant-parasitic nematodes are important pests on carrot (Daucus carota) in Malino Highland. This research aimed to identify plant-parasitic nematodes on carrot. The identification was carried out based on the morphological and morphometric characters of second-stage juveniles that were extracted from soil samples. Nematodes were extracted using the flotation-centrifugation technique. Morphometric measurement included body length, stylet length, esophagus length from the basal knob to the esophagus end, tail length from the posterior end to the anus, anterior diameter, maximum body diameter, and posterior diameter. Three genera of plant-parasitic nematodes were identified as Meloidogyne, Rotylenchulus, and Pratylenchus.